Cover Image, Volume 121, Number 4, April 2020. Issue 4 (27th February 2020) - Cheng, Yanping; Yang, Sheng; Shen, Bo; Zhang, Yan; Zhang, Xiaomei; Liu, Tong; Xu, Siyi; Sui, Jing; Yin, Lihong; Pu, Yuepu; Liang, Geyu
Abstract : Front Cover : The cover image is based on the RESEARCH ARTICLE Molecular Characterization of lung cancer: A two‐miRNA prognostic signature based on cancer stem‐like cells related genes by Yanping Cheng et al., https://doi.org/10.1002/jcb.29525 .